Answer:
So the solution of the equation will be
Explanation:
We have given polynomial
![(2x-2)(3x+1)(x-1)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/h5du88789hzcxvrc0xhn91cgcvwv58x91l.png)
We have to find all the solution of the equation
For finding the solution we have to equate the factor of the polynomial equal to zero
So
x =1
![3x+1=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lzpdfdgzj5jghl4vxnvd7zfpn97bc3jbvi.png)
![x=(-1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/tc5m9i2lj5da8adhe72pah303u6a23unbr.png)
![x-1=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/g5q82lqzt6608get6or19n6mgydda94xsc.png)
x= 1
So the solution of the equation will be
![x=1,(-1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/zov6iag89pidvs5zytym50v30zovqjz18j.png)